Prevalence study of clinical disorders in 6-year-old children across Iranian provinces: Findings of Iranian national health assessment survey - Amiri, Masoud (Medknow Publications & Media Pvt Ltd, 2012)
OBJECTIVE: To assess the national prevalence of clinical disorders in 6-year-old Iranian children before school entry using a national health assessment survey. MATERIALS AND METHODS: In a cross-sectional nationwide survey, all Iranian children entering public and private elementary schools were asked to participate in a mandatory national screening program in Iran in 2009 in two levels of screening and diagnostic levels. RESULTS: The study population consisted of 955388 children (48.5% girls and 76.1% urban). Of the whole children, 3.1% of the 6-year-old children had impaired vision. In addition, 1.2, 1.8, 1.4, 10, 10.9, 56.7, 0.7, 0.8 and 0.6% had color blindness, hearing impaired, speech disorder, height to age retardation, body mass index extremes, decayed teeth, having disease with special needs, spinal disorders, and hypertension, respectively. The distribution of these disorders was unequally distributed across provinces. CONCLUSIONS: Our results confirmed that the prevalence of clinical disorders among 6-year-old children across Iranian provinces was not similar. The observed burden of these distributions among young children needs a comprehensive national policy with evidence-based province programs to identify the reason for different distribution among provinces.